2013
DOI: 10.1111/plb.12001
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses and ion accumulation in the halophytic legume Prosopis strombulifera are determined by Na2SO4 and NaCl

Abstract: Halophytes are potential gene sources for genetic manipulation of economically important crop species. This study addresses the physiological responses of a widespread halophyte, Prosopis strombulifera (Lam.) Benth to salinity. We hypothesised that increasing concentrations of the two major salts present in soils of central Argentina (Na2SO4, NaCl, or their iso-osmotic mixture) would produce distinct physiological responses. We used hydroponically grown P. strombulifera to test this hypothesis, analysing growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 43 publications
7
37
0
2
Order By: Relevance
“…Plants grown in the presence of Na2SO4 showed immediate and sustained reduction of growth parameters, accompanied by senescence symptoms such as chlorosis, necrosis, and leaf abscission Reginato et al 2014). In this study, root length, shoot height and number of leaves of Na 2 SO 4 -treated plants were also more affected than those in NaCl-treated plants, confirming previous observations on the inhibition and toxicity induced when sulfate anion is present in the medium.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Plants grown in the presence of Na2SO4 showed immediate and sustained reduction of growth parameters, accompanied by senescence symptoms such as chlorosis, necrosis, and leaf abscission Reginato et al 2014). In this study, root length, shoot height and number of leaves of Na 2 SO 4 -treated plants were also more affected than those in NaCl-treated plants, confirming previous observations on the inhibition and toxicity induced when sulfate anion is present in the medium.…”
Section: Discussionsupporting
confidence: 79%
“…Atriplex leucoclada had maximum ABA/IAA ratio as well as higher K + /Na + ratio and higher proline and protein contents, while Haloxylon salicornicum and Salicornica verginica had lower K + /Na + ratio, lower ABA/IAA ratio as well as lower proline and protein content (Samiullah and Bano, 2011). In P. strombulifera higher ABA/IAA ratio was observed only in Na 2 SO 4 treated plants, however, no increased K + /Na + ratio or proline and protein content was observed (Reginato et al, 2014;Llanes et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previously many studies has been well reported close and positive correlation between antioxidant capacity and crops salinity tolerance (Hernandez et al, 2010, Rezazadeh et al, 2012Reginato et al, 2014b;Hand et al, 2017). Also application of potassium enhances plant vitality under stressful condition by increasing antioxidant levels and reducing ROS production (Cakmak 2005;Devi et al, 2012).…”
Section: Methodsmentioning
confidence: 99%